Business Model Innovation: A Bridge Between Corporate Social Responsibility and Successful Performance for Medium-Size Enterprises (SMEs) in the Digital Era - Mohammadsadegh Omidvar; Maria Giovanna Confetto; Maria Palazzo (Systems)
Business model innovation (BMI) is a topic that has attracted significant interest from both researchers and academics. While research has suggested that there are associations between BMI and corporate social responsibility (CSR), as well as between BMI and firm performance (FP), we lack theoretical substantiation and empirical verification of these relationships. This study proposes that BMI mediates the link between CSR and FP. This research aims to investigate the mediating role of BMI between various aspects of CSR, introduced by Carroll, and the performance of medium-size enterprises (SMEs) in Iran. To achieve the research aim, 483 questionnaires were gathered from SMEs in Iran. To evaluate the conceptual model’s validity, structural equation modeling (SEM) was used. The results of this study show that BMI mediates the relationship between all the aspects of CSR introduced by Carroll and FP and only does not mediate the relationship between the environmental dimension and FP. As far as we know, this investigation is among the earliest to explore the relationship between BMI and CSR dimensions through mediation. In response to the increasing significance of environmental issues, this research incorporates a fresh element, namely environmental responsibility, into Carroll’s model. Managers can gain a better understanding of CSR and its impact on FP from the results of this research. This study reveals that managers emphasize certain aspects of CSR which can influence BMI and FP.